Manajemen Waktu Mahasiswa Yang Bekerja Paruh Waktu: (Studi Fenomenologi) - Agatha Okta Hardani (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The study was designed to : (1) Explore the strategies used by studente who work part-time in managing time and setting prioritie, (2) Assess the professionalism of students who work part-time, (3) Know the psychological conditions experienced.The method used is qualitative research with data collection techniques in form of interviews with 2 subjects who match the research criteria. The data analysis technique is based on interview transcripts with the subject, data reduction that has been validated by the subject, data exposure as well as data presentation, and conclusions.The results showed that both subjects could manage time management between college and work activities. If based on the aspects of time management, both subjects show similar aspects aspects and are able to carry out time management. (1) The time management of the two subjects through the strategies used in time management, (2) The attitude of professionalism shown, and (3) How to manage personal/psychic conditions.